Extração por solventes sinérgica aplicada à separação níquel/cálcio utilizando-se os extratantes Cyanex 272 e D2HEPA - Marcel Felipe Alves de Souza (2015)
The present work examined the synergistic extraction solvent applied to the separation of calcium and nickel present in synthetic aqueous sulfuric solutions using the commercial organophosphorus extractants D2EHPA (di-2-ethylhexyl phosphoric acid) and Cyanex 272 (bis-2,4,4 -trimethylpentyl phosphinic acid), diluted in n-heptane. The objective was to evaluate the effects of competition between metals in the aqueous phase and between the extractants in the organic phase, both individually and simultaneously. To this end, extractions were analyzed using combinations of mono and bicomponents aqueous phases (only calcium or nickel, and both metals together), and mono and bicomponents organic phases (D2EHPA or Cyanex 272 alone, and both extractants together). Extraction tests were performed at a temperature of (25±2)°C and the volume ratio of phases of unity (A/O = 1), varying the pH from 3.5 to 7.0. The operational parameters used in the analysis of the results were the percentage of metals extraction and calcium/nickel selectivity. Samples of the organic phase were analyzed by Fourier Transform Infrared Spectroscopy (FT-IR) and Raman spectroscopy, in order to infer on the structures of the organometallic species formed during extraction. With regard to competition in the aqueous phase, it was observed that the presence of nickel, at equimolar concentrations of calcium does not interfere with calcium extraction independently of the extractor system used (Cyanex 272, D2EHPA, or D2EHPA + Cyanex 272). The nickel extraction in the presence of calcium is shifted to higher pH values using D2EHPA, as well as with the mixture of extractants. With Cyanex 272, the nickel extraction in the presence of calcium also was changed, but in a small proportion. With respect to competition in the organic phase, it was observed that the extraction curves of metals using the mixture of extractants are similar to those obtained when using only D2EHPA, indicating that it is the main reagent for the extraction of metals by mixing Cyanex 272 + D2EHPA. However, the presence of Cyanex 272 in the bicomponent organic phase favors nickel extraction compared to extraction by D2EHPA, in the presence of calcium, from pH 5, even if the metal extraction by Cyanex 272 separately is not significant in the range of pH evaluated. The mixture Cyanex 272 + D2EHPA is more selective for calcium to nickel (3.5 pH 5.0) compared to extractants separately, reaching a maximum value at pH 4.5. In this pH, the separation factor Ca /Ni with the mixture of extractants is about 17 times higher than with D2EHPA and almost 800 times higher than with Cyanex 272. This result is due to the synergism occurred between extractants, therefore the extractor system proposed is more efficient than the extractants used individually in the evaluated conditions. The FT-IR spectrums of Cyanex 272, D2EHPA and n-heptane obtained corroborated literature, but the analysis of samples loaded organic phase under the conditions studied was inconclusive about the structures formed due to the low concentrations of organic complexes obtained.